Dyschromatosis symmetrica hereditaria (reticulate acropigmentation of dohi): First report from Iran - Barzegari Massoumeh; Kiavash Katrin (Wolters Kluwer Medknow Publications, 2009)
Dyschromatosis symmetrica hereditaria (DSH) is a rare autosomal dominant genodermatosis, presenting in infancy or early childhood with areas of hyperpigmentation on dorsa of hands and feet. DSH has been reported mainly from Japan and only limited cases have been reported from other countries. This is the first report of an Iranian patient with this rare type of acropigmentation. Our patient′s family history was striking with the same disorder in her grandmother, mother, uncle and her two older sisters which reveal an autosomal dominant pattern of inheritance.